The Effectiveness of Telenursing on The Patient’s Quality of Life: A Review - Yusshy Kurnia Herliani; Alisya Putri Shabrina; Nadia Putri Andrini; Ananda Fairuz Melawardani; Hani Aisya Rahmi; Muhammad Rifki Maulana (Journal of Nursing Science Update (JNSU), 2021)
COVID-19 is a pandemic case that has occurred throughout the world, resulting in restrictions on human activity in all areas, including health services, so that telenursing is one of the long-distance health service solutions in providing interventions. Improved quality of life is an indicator of successful intervention in patients. The study aimed to identify the effectiveness of telenursing in patients' quality of life. This study was conducted using a literature review method with the keywords "effectiveness," "quality of life," and "Telenursing." Several databases were used to find articles, including Ebsco, Google Scholar, Pubmed, and ScienceDirect. Selected articles were published from 2015 to 2020 and resulted in 2060 articles. After three selection processes, ten articles were obtained accordingly. Telenursing can be used to improve the quality of life of patients suffering from a variety of medical conditions. Telenursing plays a role in improving patients' quality of life in physical, mental, and social aspects. Various applications such as WhatsApp, Telegram, and Direct Call are used to conduct telenursing. Nurses can use telenursing to give intervention so that patients can improve their quality of life in physical, mental, and social aspects during a pandemic.